X-Ray Investigation of Strain in Cold-Worked Silver Iodide - Burley, G. (J Res Natl Bur Stand A Phys Chem, 1964)
The experimentally observed broadening of certain powder diffraction profiles of cold-worked hexagonal silver iodide has been graphically resolved into the effects due to small domain size and to lattice strain. The contribution from the first was found to be negligible, and the total intrinsic broadening is thus due to strain. A maximum, or saturation value, of strain is rapidly attained and remains invariant with further grinding. The strain is essentially isotropic, with an average value of 4.4×10(−3). The calculated stored elastic energy is 154 cal/mole and, by comparison with the calculated difference in lattice energies of 149 cal/mole, can be interpreted as an energy barrier for the phase transition from the cubic to hexagonal structure.